Selection of design variables using complex proportional assessment and analysis of a rear underride protection device - Albahash Z.F.; Ansari M.N.M. (Taylor and Francis Ltd., 2023)
ABAQUS; Automobiles; C (programming language); Energy absorption; Finite element method; Trucks; Complex proportional assessments; Design variables; Fatal accidents; FMVSS 223/224; Passenger compartment; Protection device; Structural behaviour; Termination time; Accidents